The Influence of Atmosphere, Price, and Service Quality towards Customer Loyalty at Koral Restaurant of Apurva Kempinski, Bali - Angelia Djingga; Angeline Roosaris; Bernardine Inggrid Dakhi; Clarence Chenvona; Gabriella; Vicky Florent (MultiTech Publisher, 2020)
The abstract of